Augmented Reality-Based Computer Hardware Assembly Simulation Learning Media Design at SMK N 1 Bukittinggi - Hari Okto Mandiri (Journal of Computer Science Advancements, 2023)
This research is based on the results of observations that the author did at SMK N 1 Bukittinggi. From the results of observations the authors know that in the subject of Basic Network Computers do not use learning media in the learning process. The learning process is carried out in the form of direct practice accompanied by an explanation from the subject teacher. This is seen as less effective in its implementation. Thus the purpose of this study is to design learning media for computer assembly using Augmented Reality technology in order to increase the effectiveness of the learning process. The research method used is the Research and Development (R&D) research method, which is a method used to produce products. The R&D model used is the 4D version, namely, define, design, develop, desseminate with the Luther Sutopo development model which consists of 6 stages, namely conceptualization (concept), design, material collection, manufacture (assembly), testing (testing), distribution (distribution). ). And the product test consists of 3 tests, namely validity test, practicality test, and effectiveness test. Based on the results, the author succeeded in designing Augmented Reality-based assembly learning media. This learning media can be used by teachers and students in Basic Computer Networking subjects. The form of this learning media is an application (apk) that is run using Android, while the validity results obtained from 3 validators are 0.86 which is declared valid, the practical results obtained from 2 examiners are 85.33 which are declared practical, and effectiveness was obtained from 10 students 0.87 which was declared effective.